Nutritional Profiling and Heavy Metal Analysis of Withania Somnifera Based Polyherbal Formulation- Aswagandhadi Lehyam: Life Sciences-Biotechnology for prospective medical science - Ben Raj; S.R Madhan Shankar (International Journal of Life Science and Pharma Research, 2022)
Aswagandhadi lehyam, is one of the most popular formulations prescribed as Rasayana (tonic) in the traditional medical system of India, Ayurveda. As like other lehyam formulations, Aswagandhadi lehyam prepared as per the avaleha Kalpana in ayurveda. The formulation received its name from its major ingredient, Ashwagandha (Withania somnifera). Even though the Aswagandhadi lehyam used generally as rasayana, its major ingredient Ashwagandha has various medical benefits. Ashwagandha is compared well with Eleutherococcus senticosus (Siberian Ginseng) and Panax Ginseng (Chinese / Korean Ginseng) in its adaptogenic properties, and hence it is popularly known as Indian Ginseng. Since it is used as majorly as rasayana, in addition to its pharmacological studies and chemical standardisation its nutritional profiling also needs to be studied. In the present study the nutritional profiling of the Aswagandhadi lehyam is studied, which will provide a better idea regarding the nutritional values while consumed generally for increasing physical strength, endurance, stamina, vitality and vigor. It is also important to have an understanding regarding the heavy metal contamination of the formulation. Heavy metal analysis of the formulation is done in Inductively coupled plasma mass spectrometry (ICP-MS). The aswagandhadi lehyam prepared as per avaleha kalpana and Sahasrayogam, is regarded as the industrial working standard, and is considered for the study.. The organoleptic analysis reported - as smooth, dark brown sweet product, pleasant aroma and creamy texture. Nutritional profiling results evidenced the health benefits of the formulation including 389 kCal of energy value, 2.1% fibre content etc. Heavy metal contamination study done with ICPMS reported the presence of trace elements like Mercury (Hg), Arsenic (As), Lead (Pb), and Cadmium (Cd) in a range of 0.02-0.39 ppm.